Calorimetric Study of High-Volume Fly Ash-Cement Paste Hydration at Different Temperatures - Senle Huang; Jikai Yao; Yang Yang; Chunping Gu; Jintao Liu; Deyu Kong; Xiaodong Wen (Crystals, 2022)
The study on the hydration process of cement-based materials is of significance since it determines the development of the macro-properties. The hydration process of high-volume fly ash (FA)-cement based materials is quite special and needs systematic study. In this study, the hydration heat release of cement paste with high volume FA were measured with isothermal calorimetry at different temperatures. The full-width at half-maximum (FWHM) value of the exothermic peak and the cementitious index (CMI) of FA were used comprehensively to evaluate the influence of FA on cement hydration. It was found that increasing the FA content and water-binder ratio retarded the hydration process for paste but did not show obvious effects on the hydration of cement. The CMI values show that raising the temperature intensified the retarding effect of FA on cement hydration during the induction period, but promoted the subsequent hydration process. According to the normalized heat release to cement, and the change of CMI values with temperature, new evidence was found that FA may not act as nucleation sites during the hydration process of cement. The result can be better explained by the topochemical reaction mechanism.